2019
DOI: 10.20396/bjos.v18i0.8655147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for denture stomatitis in complete denture wearers

Abstract: Aim: The prevalence of denture stomatitis and the relationship with its risk factors was evaluated via secondary data from 62 complete denture (CD) wearers, between 2015 and 2017. Methods: The data was stored in an Excel database and was analyzed using the statistics software STATA/SE 12.0. A descriptive analysis was performed taking into account a categorization of the clinical variables according to risk factor in 4 domains:  CD usage, systemic health, hygiene habits, and usage habits. The association amongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Our results agree with Lemos et al 22 (2013), as their findings suggested that being completely edentulous or wearing non-fixed complete dentures, and regular, poor or extremely bad oral health were important features for negative self-perception of oral health with impact on the volunteer's quality of life 22 . Moreover, the oral health appreciation can be affected by general conditions such as rheumatoid arthritis 23 or local commodities, such as stomatitis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with Lemos et al 22 (2013), as their findings suggested that being completely edentulous or wearing non-fixed complete dentures, and regular, poor or extremely bad oral health were important features for negative self-perception of oral health with impact on the volunteer's quality of life 22 . Moreover, the oral health appreciation can be affected by general conditions such as rheumatoid arthritis 23 or local commodities, such as stomatitis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Local risk factors associated with denture stomatitis are dry mouth, denture age, local trauma induced by an ill-fitting or poorly fabricated dentures, poor denture hygiene, microorganisms, continuous and nocturnal denture wearing, smoking, carbohydrate-rich diets, acidic salivary pH, and sensitivity to denture materials [ 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic risk factors include debilitating physiological aging, poorly controlled diabetes mellitus, xerostomia, radiation therapy, neoplasm, nutritional deficiency, immunocompromised conditions (immunosuppression, immunodeficiency, as with HIV infection, and radiation therapy for the head and neck region), the long-term use of corticosteroids and antibiotics, and hematological disorders. These factors might contribute by compromising an individual’s resistance to combat the disease [ 7 , 9 , 14 , 15 , 21 , 22 ]. Recently, De Souza et al [ 28 ] reported that individuals with low socioeconomic status are more likely to develop DS due to poor access to routine medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Denture soft-lining materials, and other silicone materials used to make maxillofacial and voice prostheses are also susceptible to microbial colonisation, reducing the lifetime of these prostheses (Nikawa et al, 2001a;Nikawa et al, 2001b;Holmes et al, 2006;Nevzatoglu et al, 2007;Chladek et al, 2014;. Candida colonisation of dentures is associated with an increased incidence of denture stomatitis, the most common iatrogenic disorder affecting denture wearers (Budtz-Jorgensen, 1974;Arendorf and Walker, 1987;Ramage et al, 2004;Figueiral et al, 2007;Pereira-Cenci et al, 2008;Skupien et al, 2013;Yarborough et al, 2016;Morel et al, 2019). The aetiology of denture stomatitis is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…21,35,43,[47][48][49] Candida colonization of dentures is associated with an increased incidence of denture stomatitis, the most common iatrogenic disorder affecting denture wearers. 10,[50][51][52][53][54][55][56] The etiology of denture stomatitis is multifactorial. These factors include tissue coverage from a close-fitting denture base, denture-induced trauma, continuous denture wearing, reduced salivary flow, lack of denture cleaning, age of the denture, smoking, dietary factors, pH of the denture pellicle, and the type of denture base material such as polymethyl methacrylate (PMMA), silicone and self-cure acrylic.…”
Section: Introductionmentioning
confidence: 99%